2023
DOI: 10.18554/rbcti.v8i2.7006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the provision of ecosystem services based on sidewalk tree-composition scenarios

Beatriz Lima Francisco,
Rogerio Bobrowski,
Sidnei Antonio Crovador Junior
et al.

Abstract: Cities have been experiencing environmental and social issues due to urban expansion processes, be them planned or not. However, several environmental solutions have been proposed and sidewalk tree planting stands out among them. The aim of the current research is to assess the process to estimate ecosystem services under different sidewalk tree composition scenarios in Irati and Curitiba cities, Paraná State. In order to do so, 10 street segments from neighborhoods sampled in city-wide inventories were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The study by Francisco et al (2023) "Changes in the provision of ecosystem services based on sidewalk tree-composition scenarios" shows that the ecosystem services offered by sidewalk tree planting in Irati and Curitiba is a valuable contribution to sustainable urban planning. By testing different floristic composition scenarios, the researchers identified that the choice of tree species plays a crucial role in maximizing ecosystem services, highlighting the importance of conscious decisions in urban afforestation.…”
Section: Esteemed Readersmentioning
confidence: 99%
“…The study by Francisco et al (2023) "Changes in the provision of ecosystem services based on sidewalk tree-composition scenarios" shows that the ecosystem services offered by sidewalk tree planting in Irati and Curitiba is a valuable contribution to sustainable urban planning. By testing different floristic composition scenarios, the researchers identified that the choice of tree species plays a crucial role in maximizing ecosystem services, highlighting the importance of conscious decisions in urban afforestation.…”
Section: Esteemed Readersmentioning
confidence: 99%